1980
DOI: 10.1128/iai.27.2.322-334.1980
|View full text |Cite
|
Sign up to set email alerts
|

Iron acquisition by Neisseria meningitidis in vitro

Abstract: Assays employing iron-limited solid and liquid, defined and complex media were devised to test the iron requirements of Neisseria meningitidis. A variety of tests yielded no evidence for the secretion of a soluble iron-binding substance (siderophore) by the meningococci. The meningococci were unable to use iron bound to some common hydroxamateand catechol-type siderophores or even compete with them for iron in the growth medium. A total of 20 strains of meningococci, differing widely in their virulence for mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 53 publications
1
68
1
Order By: Relevance
“…The observation that both type b and non-typable H. influenzae strains are capable of utilizing transferrinbound iron [21] suggests that these organisms may remove iron from transferrin directly and perhaps in a manner analogous to that proposed for Neisseria spp. [11,25,26]. Alternatively, H. infiuenzae may constitutively produce siderophores together with OM receptor proteins, Thus the ability of H. influenzae type b strains and its absence from the OM of the non-typable strains is not yet apparent.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that both type b and non-typable H. influenzae strains are capable of utilizing transferrinbound iron [21] suggests that these organisms may remove iron from transferrin directly and perhaps in a manner analogous to that proposed for Neisseria spp. [11,25,26]. Alternatively, H. infiuenzae may constitutively produce siderophores together with OM receptor proteins, Thus the ability of H. influenzae type b strains and its absence from the OM of the non-typable strains is not yet apparent.…”
Section: Resultsmentioning
confidence: 99%
“…obtain iron from their host environment by a process that differs from the typical siderophore-mediated mechanism described for many other pathogens (Norrod and Willams, 1978;Mickelsen and Sparling, 1981;Mickelsen etat., 1982;Mietzner and Morse, 1983;West and Sparling, 1985;Schryvers and Morris, 1988a,b;Lee and Schryvers, 1988). At least two alternative mechanisms have been proposed, Archibald and DeVoe (1980) suggested that 'functional siderophores', produced by the human host or by the infecting organisms as biproducts of cellular metabolism might participate as iron-chelators. These compounds should be available in high concentrations and could initiate the process of iron-uptake.…”
Section: Discussionmentioning
confidence: 99%
“…pestis uses haemin and a wide variety of host haemcontaining complexes including haemoglobin, haemoglobin-haptoglobin, myoglobin, haem-haemopexin, and haem-albumin as sources of iron (Perry and Brubaker, 1979;Sikkema and Brubaker, 1989;Staggs and Perry, 1991). In addition to Y. pestis, a number of pathogenic bacteria including the enteropathogenic yersiniae (Perry and Brubaker, 1979;Stojiljkovic and Hantke, 1992), Vibrio species (Helms et a/., 1984;Mazoy and Lemos, 1991;Stoebner and Payne, 1988;Yamamoto eta/., 1995), Haemophilus species (Coulton and Pang, 1983;Lee, 1991 ;Stull, 1987), Neisseria species (Archibald and DeVoe, 1980;Dyer et a/., 1987;Mickelsen and Sparling, 1981), Campylobacter jejuni (Pickett et a/. , 1992), Helicobacter pylori (Hazel1 et a/., 1986), Plesiomonas shigelloides (Daskaleros et a/., 1991), Shigella dysenteriae (Mills and Payne, 1995), Klebsiella pneumoniae (Ward et a/., 1986), enteropathogenic Escherichia coli strains (Law et a/., 1992), Porphyromonas gingivalis (Bramanti and Holt, 1991), Serratia marcescens ( Letoffe et a/., 1994), and Streptococcus pneumoniae (Tai et a/.…”
Section: Introductionmentioning
confidence: 99%